Faktor-Faktor yang Mempengaruhi Permintaan Ikan Laut di Desa Jetis, Kecamatan Nusawungu, Kabupaten Cilacap - Dian Ajic Astoro; Lilis Siti Badriah; Goro Binardjo (Universitas Batanghari Jambi, 2023)
Cilacap Regency has a fairly high production of marine fish, but it is not matched by the high level of consumption of marine fish by its people. However, based on data per village, Jetis Village in Nusawungu District is the highest village in terms of consumption of marine fish when compared to other areas. Therefore, it is interesting to study the factors that influence the demand for marine fish in Jetis Village, Nusawungu District, Cilacap Regency. The purpose of this study was to analyze the effect of the price of marine fish, the price of other goods, income, and the number of household members on the demand for marine fish in Jetis Village, Nusawungu District, Cilacap Regency. This study uses primary data obtained through interviews and distributing questionnaires to 96 households in Jetis Village. Data were analyzed using multiple linear regression model. The results showed that the price of marine fish and income, did not have a significant effect on the demand for marine fish in Jetis Village. Meanwhile, the price of other goods and the number of household members have a significant influence on the demand for marine fish in Jetis Village. The implication of this research is that although the price of marine fish has no significant effect on the demand for marine fish, the stability of the price of marine fish is still important for the community so that the price of marine fish will remain affordable. Since the prices of other goods are complementary to the consumption of marine fish, it is important to pay attention to price stability for other goods, such as the price of chicken meat, the price of freshwater fish, and the price of eggs.